An examination of the Iridovirus core genes for reconstructing Ranavirus phylogenies - D.R. Ballard; A.J. Davis; R.B. Fuller; A.R. Garner; A.D. Mileham; J.D. Serna; D.E. Brue; C.M. Harding; C.D. Dodgen; W. Culpepper; B. Piatt; S.E. Rosario; et al. (Canadian Science Publishing, 2020)
Ranaviruses are globally emerging infections of poikilothermic vertebrates and belong to the viral family Iridoviridae. The six species of ranaviruses are responsible for unknown numbers of infections and disease and mortality events around the world in amphibians, fish, and reptiles. Genomic investigations have shown that there are 24 core genes shared by all iridoviruses. In this study, we examine the utility of each of these genes in reconstructing phylogenetic relationships across six species of Ranavirus. We also performed dot-plot analysis for the 17 isolates in the study. For large-scale differentiation, using the major capsid protein gene creates a tree similar to the whole genome tree. Other comparable genes include open reading frame (ORF) 19R (a serine-theonine protein kinase) and ORF 88R (Erv I/Alr Family protein). The poorest candidate for phylogenetic reconstruction, due to high homology, was ORF 1R (a putative replication factor and (or) DNA binding-packing protein). There are a plethora of genes that may be useful to examine phylogenies at smaller scales (e.g., to examine local adaptation); however, they do not necessarily belong to the set of highly conserved core genes.